Molecular Modeling Investigation of Some New 2-mercaptoimidazoles - Rani, Nidhi; Singh, Randhir (Current Computer - Aided Drug Design, 2017)
Background: Docking study has become an important and interesting tool for the investigation of drug- receptor interaction. Computational methodologies have become a crucial component in the drug discovery programs which involves identification of target and lead along with their ADME and pharmacokinetic studies so as to obtain a potent lead. Objective: Synthesis and Molecular modeling investigation of some new 2-mercaptoimidazoles. Method: New 2- mercaptoimidazoles were synthesized via solid phase synthesis and were characterized by spectral studies i.e IR, 1NMR, Mass spectra and LC-MS. Compounds were screened for their antimicrobial potency via agar well diffusion assay against three bacterial strains and two fungal strains. Compounds were subjected to molecular docking studies for rationalization of their mode of action. Results: 18 new imidazole derivatives having mercapto group (4a-r) were synthesized via solid phase synthesis and were characterized by spectral studies i.e IR, 1NMR, Mass spectra and LC-MS. All the compounds were found to possess promising antimicrobial potency. However, compounds 4j and 4k were found to be the most potent compounds of the series against al the tested strains. The in silcio molecular modeling study results indicated that all the compounds exhibited good affinity towards the active site and thus may be considered as good inhibitors of enzyme 14α-demethylase. Conclusion: Thus, it may be concluded that the compounds are good inhibitors of enzyme 14α- demethylase and may be further investigated to obtain antimicrobial lead.
Keywords: mercaptoimidazole